Sistem Informasi Eksekutif Perpustakaan Dengan Fitur Drilldown Dan Analisis What-If - Feby Dwiputra Setyawan; Agung Brastama Putra; Seftin Fitri Ana Wati (Pusat Riset dan Inovasi Nasional, 2024)
Every agency or company needs to adapt to information technology so that it can provide opportunities to increase its competitive advantage in the future. The use of technology has an impact on the activities of an agency or company, including executive information systems. The Library Executive Information System for UPA Perpustakaan Universitas Pembangunan Nasional